Perga under compressive loading - Kubík Ľubomír; Brindza Ján; Brovarskyi Valeryi; Velychko Serhii (Journal on Processing and Energy in Agriculture, 2017)
Paper dealt with the experimental testing of the perga cylinder samples at the compressive loading in the longitudinal direction. The perga is bee product and it represents the material created from the bee pollen by means of the lactic fermetation. Mechanical properties such as the failure stress and strain as well as the modulus of elasticity can be used to evaluate the behaviour of the perga pellets mechanically under the static loading. A testing machine Andilog Stentor 1000 (Andilog Technologies, Vitrolles, France) was employed for compression tests. The samples of the perga have been tested at the different strain rates and the behaviour at the constant speed was compared with the behaviour at the different loading speeds. The experiments were performed at eighteen velocities from 10 to 270 mm.min-1 in order to achieve the different strain rates. The influence of strain rate on the stress was studied.